Inscribed Bonanza

Geometry Level 4

Let V s , V p , V c V_{s}, V_{p}, V_{c} and V m V_{m} be the volumes of the sphere, right circular cone, right circular cylinder and square pyramid respectively so that:

V p V_{p} is the volume of the largest right circular cone inscribed in the sphere of volume V s V_{s}

V c V_{c} is the volume of the largest right circular cylinder inscribed in the right circular cone of volume V p V_{p}

and

V m V_{m} is the volume of the largest square pyramid inscribed in the right circular cylinder of volume V c V_{c} .

If V p V c V m V s 3 = 1 π ( a b ) \dfrac{V_{p} * V_{c} * V_{m}}{V_{s}^3} = \dfrac{1}{\pi}(\dfrac{a}{b}) , where a a and b b are coprime positive integers, find a + b a + b .


The answer is 4799353.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Jan 26, 2019

Let V s = 4 3 π R 3 , V p = 1 3 π r 2 H , V c = π x 2 h V_{s} = \dfrac{4}{3}\pi R^3, \:\ V_{p} = \dfrac{1}{3}\pi r^2 H, \:\ V_{c} = \pi x^2 h and V m = 1 3 y 2 h V_{m} = \dfrac{1}{3}y^2 h .

R 2 = ( H r ) 2 + r 2 = H 2 2 H R + R 2 + r 2 r 2 = 2 H R H 2 V p = 1 3 π ( 2 H 2 R H 3 ) R^2 = (H - r)^2 + r^2 = H^2 - 2HR + R^2 + r^2 \implies r^2 = 2HR - H^2 \implies V_{p} = \dfrac{1}{3}\pi(2H^2R - H^3) \implies

d V p d H = π 3 R H ( 4 R 3 H ) = 0 H 0 H = 4 3 R r = 2 2 3 R V p = ( 2 3 ) 3 V s \dfrac{dV_{p}}{dH} = \dfrac{\pi}{3}RH(4R - 3H) = 0 \:\ H \neq 0 \implies H = \dfrac{4}{3}R \implies r = \dfrac{2\sqrt{2}}{3}R \implies \boxed{V_{p} = (\dfrac{2}{3})^3 V_{s}}

The two triangles in the above diagram are similar r x r = h H h = ( r x ) H r V c = π H r ( r x 2 x 3 ) d V c d x = π H x r ( 2 r 3 x ) = 0 \implies \dfrac{r - x}{r} = \dfrac{h}{H} \implies h = \dfrac{(r - x)H}{r} \implies V_{c} = \dfrac{\pi H}{r}(rx^2 - x^3) \implies \dfrac{dV_{c}}{dx} = \dfrac{\pi Hx}{r}(2r - 3x) = 0 x 0 x = 2 3 r h = H 3 x \neq 0 \implies x = \dfrac{2}{3}r \implies h = \dfrac{H}{3}

r = 2 2 3 R r = \dfrac{2\sqrt{2}}{3}R and H = 4 3 R x = 4 2 9 R H = \dfrac{4}{3}R \implies x = \dfrac{4\sqrt{2}}{9}R and h = 4 9 R V c = ( 2 3 ) 5 V s h = \dfrac{4}{9}R \implies \boxed{V_{c} = (\dfrac{2}{3})^5V_{s}}

y = 2 x y = \sqrt{2}x and x = 4 2 9 R y = 8 9 R V m = 1 π ( 2 3 ) 6 V s x = \dfrac{4\sqrt{2}}{9}R \implies y = \dfrac{8}{9}R \implies \boxed{V_{m} = \dfrac{1}{\pi}(\dfrac{2}{3})^6 V_{s}}

V p V c V m V s 3 = 1 π ( 2 3 ) 14 = \implies \dfrac{V_{p} * V_{c} * V_{m}}{V_{s}^3} = \dfrac{1}{\pi}(\dfrac{2}{3})^{14} = 1 π ( 16384 4782969 ) = 1 π ( a b ) a + b = 4799353 \dfrac{1}{\pi}(\dfrac{16384}{4782969}) = \dfrac{1}{\pi}(\dfrac{a}{b}) \implies a + b = \boxed{4799353} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...